Endoplasmic Reticulum-Targeted Ratiometric N-Heterocyclic Carbene Borane Probe for Two-Photon Microscopic Imaging of Hypochlorous Acid - Pak, Yen Leng; Park, Sang Jun; Song, Gyeongok; Yim, Yubin; Kang, Hyuk; Kim, Hwan Myung; Bouffard, Jean; Yoon, Juyoung (Analytical Chemistry, 2018)
The naphthoimidazolium borane 4 is shown to be a selective probe for HOCl over other reactive oxygen species. Unlike other boronate-reactive oxygen species (ROS) fluorogenic probes that are oxidized by HOCl through a nucleophilic borono-Dakin oxidation mechanism, probe 4 is distinguished by its electrophilic oxidation mechanism involving B-H bond cleavage. Two-photon microscopy experiments in living cells and tissues with the probe 4 demonstrate the monitoring of endogenous HOCl generation and changes in HOCl concentrations generated in the endoplasmic reticulum during oxidative stress situations.
Keywords: Electrophilic oxidation; Endoplasmic reticulum; Fluorogenic probes; Microscopic imaging; N-heterocyclic carbenes; Oxidation mechanisms; Reactive oxygen species; Two photon microscopy; Animals; Boranes; Cell Line, Tumor; Endoplasmic Reticulum; Fluorescent Dyes; Humans; Hydrolysis; Hypochlorous Acid; Imidazoles; Male; Mice; Microscopy; Oxidation-Reduction; Rats, Sprague-Dawley; RAW 264.7 Cells; Ultraviolet Rays